ANALISIS HAMBATAN PROSES PEMBELAJARAN BIOLOGI SECARA DARING SELAMA PANDEMI COVID-19 DI SMA NEGERI - Fitriani Fitriani; Risma Delima Harahap; Islamiani Safitri (Universitas Islam Negeri Sumatera Utara, 2022)
The aim of this study is to know the obstacles of online biology learning for class XI-Science students in SMAN 1 Sei Kanan during the Covid-19 Pandemic. This study used a descriptive qualitative approach. The subjects of this study were students in class XI-Science of the school. The data collection technique used was questionnaires distributed to the students. The data analysis showed there were some obstacles in biology learning based on indicators as follow; students’ motivation in online learning at a rate of 62.73%, online learning methods at a rate of 52.81%, internet network at a rate of 42.91%, and students’ understanding in learning at a rate of 57.79%. Those were the obstacles for students and teachers when using online learning.